Medical imaging system with a fixed array of x-ray detectors and a fixed array of x-ray emitters for producing a digital 3-dimensional image - Hauser, R; Travish, G; Patel, K (World Intellectual Property Organization, 2017)
The individual emitters are operated in multiple groups each illuminating a region of interest between the emitter array and the detector array such that the cone of radiation rays projected on the detector array from any single emitter in any one such group is substantially spatially separated from the corresponding projected cones from all other emitters in that same group. At least the ROI portion of the 3D space between the emitter panel and the detector panel is represented by 3D volume elements (voxels), wherein at least some of those voxels represent respective portions of that space that are traversed by corresponding portions of a plurality of radiation rays each extending from a respective emitter to a respective detector and are associated with respective absorption coefficients representative of the radiation absorption characteristic of a corresponding portion of the ROI. The image reconstruction process is an iterative process in which neighboring voxels having similar calculated coefficients are combined into larger voxels, neighboring voxels having dissimilar calculated coefficients are divided into smaller voxels, and new absorption coefficients are calculated.